Color tuning in inverted blue light-emitting diodes based on a polyfluorene derivative by adjusting the thickness of the light-emitting layer. Issue 38 (8th September 2015) - Xu, Jin; Yu, Lei; Hu, Liwen; He, Ruifeng; Yang, Wei; Peng, Junbiao; Cao, Yong
Abstract : The EL spectra possessed high adjustability with the variation of thickness of the emissive layer in the IPLEDs. Abstract : Inverted blue polymer light-emitting diodes (IPLEDs) were fabricated by using polyethylenimine ethoxylate (PEIE) as the interlayer and a polyfluorene derivative (PF-FSO10) as the emissive layer, with the device structure of ITO/ZnO/PEIE/PF-FSO10/MoO3 /Al. Upon insetting the PEIE interlayer, the maximum luminous efficiency (LEmax ) of the IPLEDs increases by about three orders of magnitude, compared with that without. The enhancement of device performance could be attributed to the effective electron-injecting/hole-blocking ability of PEIE, and less exciton quenching at the interface of ITO/ZnO/PEIE. As the thickness of PF-FSO10 is tuned, the color coordinates of the devices can change from sky blue (0.18, 0.26) to deep blue (0.16, 0.07), and the LEmax of the devices can also be improved from 1.77 to 5.7 cd A −1, which should contribute to the micro-cavity effects and the expansible recombination zone, respectively. These results provide an excellent method to improve the efficiency and color purity of the inverted blue-light emitting diodes.